Application of EFA and AHP in the Last-Mile Delivery Service in Thailand - Waralee Rattanakijsuntorn (My University, 2023)
Significant growth in electronic commerce in the 2010s has led to substantial expansion in last-mile delivery service for packages. Shifts in people's daily lifestyles also stimulate demand for the delivery of groceries and ready-to-consume meals. While the increasing number of last-mile delivery service providers offers customers more alternatives, the decision-making process involves more factors than just price and time. This paper aims to reveal factors affecting the decision to select last-mile delivery service providers by using exploratory factor analysis and analytical hierarchy process. Data were collected in two periods for differential analysis. It has been found that apart from price, quality, and time, customers are also concerned about the safety of online transactions and service innovation. Alarmingly, the environment is the least influential decision factor, leading to recommendations to further investigation on green practices awareness in the industry.
Keywords: Urban and Freight Transport Logistics; Consumer Retail Behavior Studies; E-commerce and Technology Innovations